BELAJAR TARI TRADISIONAL DALAM UPAYA MELETARIKAN TARIAN ASLI INDONESIA - Jamalul Lail (Asian Journal of Innovation and Entrepreneurship, 2015)
Efforts to preserve the national culture through traditional dances should beencouraged, especially in children. This reason  makes writer interested in doing community service programs in the form of traditional dance training for dusunSentono. It is given because children nowadays have only bit understanding about traditional dance.